El Presidente tries you: the mechanisms of gamers’ productivity capitalization in “Tropico”, “Torchlight” and “Diablo” video game series - Felczak, Mateusz (Replay. The Polish Journal of Game Studies, 2015)
In popular economic discourse, productivity is the ratio of the value of manufactured goods to the initial input. In games, the input can be placed on the players’ side: players invest their time, financial resources, and cultural capital in order to achieve certain benefits, which are “produced “ in the course of the game. The status of this benefit is dependent on the context, but developers make such players’ productivity a key strategy used in promoting and maintaining a game and its fan base. The paper analyses three games: "Tropico III", "Diablo III" and "Torchlight II", in the context of ideological underpinnings of game mechanics that support the notions of using fan’s free labour, taking advantage of their non-game activities via the auction house and forcing them to internalize neo-colonial stance, respectively.